New Methodology for Optimal Operation of Soil Aquifer Treatment Systems - Li, Guihua; Tang, Zongwu; Mays, Larry W.; Fox, Peter (Water resources management, 2000)
A new methodology is presented in this article for computing the optimal operation of soil aquifer treatment systems. The mathematical problem is stated as a discrete-time optimal control problem to maximize infiltration subject to various physical and operation constraints. The methodology is based upon solving the discrete-time optimal control problem using a successive approximation linear quadratic regulator interfaced with a simulator. The unsaturated flow model HYDRUS is modified to simulate the water content distribution, the infiltration process, and the draining process. A penalty function method is used to treat the bound constraints on the water content and the cycle time. Sample problems are given to illustrate the capability of the model to solve the optimal operation of soil aquifer treatment systems.